PEMANFAATAN TEKNOLOGI DIGITAL UNTUK PEMASARAN USAHA PEMBIBITAN IKAN KONSUMSI LOKAL DI KECAMATAN BADAS - Amalia Febryane Adhani Mazaya; Hadiana Hadiana; Prasetya Eka Fitriansyah; Astri Aci Aringhi; Restu Bai Haqi (Universitas Mataram, 2026)
Badas District, Kediri Regency is one of the main centers for catfish breeding in East Java. Despite its high production potential, the main challenge faced by fish farmers is limited market access due to the continued dominance of conventional marketing methods. This situation results in low profits for farmers and even leads to losses when their production is not absorbed by the market. In the digital era, the use of information and communication technology is a strategic solution to increase product competitiveness through digital marketing. The objective of this community service activity is to provide digital marketing training to fish farmers in Badas Village, utilizing social media and e-commerce platforms to expand market reach. The implementation method includes socialization, training, mentoring, and evaluation. Socialization is carried out to provide an understanding of the importance of digital marketing, followed by training on the use of social media and e-commerce, and the creation of promotional content. Mentoring is provided so that participants can manage digital accounts sustainably. Evaluation is carried out through pre- and post-tests to measure improvements in participants' digital literacy. The results of the activity show a significant increase in participants' level of understanding. Before the training, the majority were in the